A novel gene is disrupted at a 14q13 breakpoint of t(2;14) in a patient with mirror-image polydactyly of hands and feet - Kondoh S. (2014)
Mirror-image polydactyly of hands and feet (MIP) is a very rare congenital anomaly characterized by mirror-image duplication of digits. To isolate the gene responsible for MIP, we performed translocation breakpoint cloning from an MIP patient with t(2;14)(p23.3;q13). We isolated a good candidate gene for MIP that was disrupted by the translocation of the patient. We had previously constructed a 1.2-megabase bacterial artificial chromosome (BAC)/P1-derived artificial chromosome (PAC) contig covering the 14q13 breakpoint of t(2;14)(p23.3;q13). From a 500-kb segment consisting of seven BAC/PAC clones in the contig, we isolated a novel gene (the mirror-image polydactyly 1 gene, designated as MIPOL1, GenBank Accession No. AY059470), in addition to the hepatocyte nuclear factor 3 alpha gene (HNF3A, GenBank Accession No. XM 007360). MIPOL1 spans about 350kb, comprises 15 exons, and encodes 442 amino acids. Northern blot analysis revealed that MIPOL1 expression is definite but very weak in adult heart, liver, skeletal muscle, kidney, and pancreas, and in fetal kidney. In view of the genome sequence and the contig map constructed, the 14q13 breakpoint of the patient was identified as located in intron 11 of MIPOL1, indicating that the gene was disrupted by the translocation, and that the breakage resulted in MIPOL1 protein truncation. Whole-mount in situ hybridization in mouse resulted in mouse Mipol1 signals all over E10.5-E13.5 mouse embryos. Two other unrelated patients with limb anomalies similar to MIP were subjected to mutation analysis of MIPOL1, but none had any mutations. We then isolated BAC clones from the other breakpoint, 2p23.3. A search for genes and expressed sequence tags in a more than 300-kb region around the 2p23.3 breakpoint found only the neuroblastoma-amplified protein gene (NAG, GenBank Accession No. NM 015909), which is located at least 50kb centromeric to the breakpoint and is not likely to be related to MIP. MIPOL1 is a good candidate gene for the MIP type of anomaly.